SUPPLEMENT: Transcription (ed. Fabian Huss), E. J. Moeran, Symphony No. 2 in E flat - Huss, Fabian (Journal of the Society for Musicology in Ireland, 2011)
An annotated transcription of the autograph manuscript of E. J. Moeran’s unfinished Second Symphony, published by JSMI to accompany the article by Fabian Huss in which the manuscript is discussed at length. The preface to the transcription and its list of annotations are given at the end of the article.